Becoming reflective practitioners: Mathematics student teachers' experiences - Ngololo, Elizabeth Ndeukumwa; Kanandjebo, Leena Ngonyofi (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2021)
The level of quality reflective practice remains low among student teachers majoring in Mathematics education. This paper aims to identify the levels of reflective practice possessed by Mathematics education student teachers in a teacher training program at higher learning institutions in Namibia. The professional status requires that teachers become reflective practitioners to develop their effectiveness- a skill they can acquire during their training. A reflection framework was used to identify levels of reflective practices among Mathematics student teachers. This study is qualitative and employed a narrative inquiry approach to assess the effectiveness of reflective practice as experienced by student teachers. A total of ten third-year undergraduate students majoring in Mathematics Education participated in the study by generating reflective journals. The results show that student teachers have insufficient reflective skills which are limited to the first two levels of the reflection framework: Â technical reflection and reflection-in-and-on-action. This could be due to little guidance offered on developing reflective skills and its use by student teachers. This study's findings will be used to improve the rationality, social and educational practices among the student teachers.Â Â